Legal Discourse: The Spirit of Democracy and Human Rights Post Simultaneous Regional Elections 2020 in the Covid-19 Pandemic Era - Hamdani, Fathul; Fauzia, Ana (Universitas Negeri Semarang, 2021)
The implementation of these simultaneous regional elections is certainly a separate discourse that is interesting to be learned, especially concerning the enforcement of democracy and human rights. The main objectives of this research focus on the analysis related to the relationship between democracy and human rights, the fundamental dignity of democracy and human rights after the implementation of the regional leader’s elections in 2020, and also the government’s responsibility in case of an increase in cases of Covid-19 resulting from the implementation of simultaneous regional elections. In this research, the method used is normative juridical using statutory, conceptual, and historical approaches. The research results centered on a conception of democracy and human rights as a conception of humanity born from the history of human civilization. This conception of human rights and democracy in its development is significantly related to the conception of state law. Thus, the existence of Indonesia as a legal state places the law as a hierarchicalunity of the legal norms that culminate in the constitution, and the constitution has clearly and clearly stated in Article 28I paragraph (4) of the Constitution that: “The protection, promotion, enforcement, and fulfillment of human rights is the responsibility of the state, especially the government.